¿Cómo representar la dictadura? Recorrido por estrategias cinematográficas en documentales uruguayos - Beatriz Tadeo Fuica (Les Cahiers ALHIM)
This article analyses three strategies used by uruguayan documentary-makers to represent the violence of the dictatorship (1973-1985). To achieve this aim, first, it introduces the democratic transition; then, it presents a succinct theoretical discussion on the relationship between documentary and the representation of violence ; and finally, it focuses on specific cases that allow us to reflect on the validity of representation, despite its limits. In addition to the analysis of different strategies -use of testimonies, of photographs and of re-enactments- this article explores the relationship between documentary and its production context, in a country that still has a long way to go in terms of truth and justice.